A Novel Methodology for Production Decline Analysis in Tight Gas Reservoirs: A Case Study from Sulige Tight Gas Field. (26th April 2021) - Li, Xiaofeng; Liu, Lili; Liu, Jiaojiao; Li, Zhichao; Zhao, Xiaoliang
Abstract : Study shows that decline exponents of gas wells in Sulige Tight Gas Field vary during their life cycle. However, decline analysis methods with variable decline exponent have not been developed so far. To address this problem, a simple-yet-effective method is proposed. In this method, the fracture linear flow regime and the channel linear flow regime, which appear two straight lines on the coordinate axis (1 / q vs. t ), respectively, are used to carry out the decline analysis. Each regime has a different slope and intercept (in the form of 1 / q vs. t ), which leads to a useful graphical technique for predicting gas rate. The graphical technique is verified by matching actual gas rate and predicting future gas rate trend. Theoretically, the influence of the two slopes and intercepts in the graphical technique on the rate decline is also studied. Aiming at decline analysis for tight gas wells with variable decline exponents, this paper proposes a novel method using linear flow characteristics, which ingeniously avoids the establishment of an empirical method to deal with variable decline exponent. The method in this study can help for better understanding of decline analysis of tight gas wells in a theoretical manner.